2020
DOI: 10.3390/md18100517
|View full text |Cite
|
Sign up to set email alerts
|

Viridicatol Isolated from Deep-Sea Penicillium Griseofulvum Alleviates Anaphylaxis and Repairs the Intestinal Barrier in Mice by Suppressing Mast Cell Activation

Abstract: Viridicatol is a quinoline alkaloid isolated from the deep-sea-derived fungus Penicillium griseofulvum. The structure of viridicatol was unambiguously established by X-ray diffraction analysis. In this study, a mouse model of ovalbumin-induced food allergy and the rat basophil leukemia (RBL)-2H3 cell model were established to explore the anti-allergic properties of viridicatol. On the basis of the mouse model, we found viridicatol to alleviate the allergy symptoms; decrease the levels of specific immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Its molecular formula was established as C17H18N2O4 according to the protonated molecule peak at m/z 337.1176 [M + Na] + in its (+)−HRESIMS (High Resolution Electrospray Ionization Mass Spectroscopy) spectrum, requiring ten degrees of unsaturation. The 1 H and 13 C NMR spectroscopic data (Table 1) displayed 17 carbons, characteristics of one mono-substituted aromatic unit [δH 7.24 (1H, br t, J = 7.4 Hz, H-4), 7.33 (2H, dd, J = 7.8, 7.3 Hz, H-3, 5), 7 3 Hz) confirmed the two benzene units and deduced another fragment of C-7/C-8. By the HMBC (Heteronuclear Multiple-bond Correlation) correlations of H-7 (δH 5.16) to C-1/C-2/C-6/C-9 and H-6' (δH 7.60)/7′-NMe (δH 2.89) to C-7', 1 was then assigned a phenylpropionyl moiety and a benzamide groups (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Its molecular formula was established as C17H18N2O4 according to the protonated molecule peak at m/z 337.1176 [M + Na] + in its (+)−HRESIMS (High Resolution Electrospray Ionization Mass Spectroscopy) spectrum, requiring ten degrees of unsaturation. The 1 H and 13 C NMR spectroscopic data (Table 1) displayed 17 carbons, characteristics of one mono-substituted aromatic unit [δH 7.24 (1H, br t, J = 7.4 Hz, H-4), 7.33 (2H, dd, J = 7.8, 7.3 Hz, H-3, 5), 7 3 Hz) confirmed the two benzene units and deduced another fragment of C-7/C-8. By the HMBC (Heteronuclear Multiple-bond Correlation) correlations of H-7 (δH 5.16) to C-1/C-2/C-6/C-9 and H-6' (δH 7.60)/7′-NMe (δH 2.89) to C-7', 1 was then assigned a phenylpropionyl moiety and a benzamide groups (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Its molecular formula was established as C 17 H 18 N 2 O 4 according to the protonated molecule peak at m/z 337.1176 [M + Na] + in its (+)−HRESIMS (High Resolution Electrospray Ionization Mass Spectroscopy) spectrum, requiring ten degrees of unsaturation. The 1 H and 13 C NMR spectroscopic data (Figures S1 and S2, Table 1) displayed 17 carbons, characteristics of one mono-substituted aromatic unit [δ H 7.24 (1H, br t, J = 7.4 Hz, H-4), 7.33 (2H, dd, J = 7.8, 7. 3 Hz) confirmed the two benzene units and deduced another fragment of C-7/C-8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data suggest that, in mast cells, viridicatol may inhibit Ca 2+ signaling induced by ionophores. As a consequence, viridicatol may prevent mast cell degranulation, which could block the activation of mast cells that are involved in the inflammatory response [ 14 ]. Evidence showed that viridicatol also abolishes intracellular Ca 2+ increases in rat basophilic leukemia cells and mast cells isolated from mice treated with ovalbumin to induce food allergy, thus alleviating allergic symptoms.…”
Section: Heterocyclic Marine Drugs With Effect Over Calcium Channementioning
confidence: 99%